Influence of graphene nanoplatelets on curing kinetics and rheological properties of a benzoxazine resin. (September 2020) - García-Martínez, V.; R.Gude, M.; Calvo, S.; Martínez-Miranda, M.R.; Ureña, A.
Abstract: The effect of two types of graphene nanoplatelets on the curing kinetics, gelation and vitrification behaviour of a benzoxazine resin was investigated by means of differential scanning calorimetry and rheological experiments. The results showed that the incorporation of graphene nanoplatelets did not change the autocatalytic nature of curing reaction. However, when benzoxazine was doped with the nanofiller supplied by XG-Sciences an acceleration effect in curing reaction was observed, especially when a 2 wt.% was added. This catalytic effect was demonstrated by the reduction of peak temperature, apparent activation energy and the shorter gelation and vitrification times. Finally, the curing kinetic equation for benzoxazine and its nanocomposites was obtained by linear model-fitting of non-isothermal experiments and it matched reasonably well with the experimental results from both non-isothermal and isothermal tests.